2020
DOI: 10.1371/journal.pone.0228409
|View full text |Cite
|
Sign up to set email alerts
|

Higher risk of herpes zoster in stroke patients

Abstract: Background Stroke is a leading cause of death, morbidity and disability worldwide. Infection is a common complication in the acute phase after stroke. Herpes zoster is a common viral disease, in which the most debilitating complication is post-herpetic neuralgia, which can have a very large negative impact on quality of life. The aim of this study was to investigate whether stroke increases the risk of herpes zoster. Methods This cohort study compared patients who had herpes zoster with and without a first inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The underlying mechanisms of the effect of ischemic stroke on the risk of herpes zoster are unclear. The possible explanation is that stroke leads to increased cell death and in ammatory response in the affected area, which in turn affects nervous system regulation and immune suppression, and immune system suppression increases the risk of infection with herpes zoster [14,34]. Furthermore, one possible biological explanation for the effects of herpes zoster on ischemic stroke is that herpes zoster infection involves viral invasion of the arterial wall, which causes granulomatous and necrotizing vasculitis [35].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of the effect of ischemic stroke on the risk of herpes zoster are unclear. The possible explanation is that stroke leads to increased cell death and in ammatory response in the affected area, which in turn affects nervous system regulation and immune suppression, and immune system suppression increases the risk of infection with herpes zoster [14,34]. Furthermore, one possible biological explanation for the effects of herpes zoster on ischemic stroke is that herpes zoster infection involves viral invasion of the arterial wall, which causes granulomatous and necrotizing vasculitis [35].…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of patients (18-41%) experience severe or very severe pain, which usually persists after the rash has healed (25)(26)(27). The acute and chronic pain of post-HZ neuralgia may seriously affect patients' quality of life, carry high medical costs, and interfere with patients' physical, emotional and social functions (28).…”
Section: Discussionmentioning
confidence: 99%
“…The infection during pregnancy could be transmitted to the fetus easily and may result in congenital varicella syndrome or childhood herpes zoster 15 . VZVI can be affected by various patient‐related factors such as diabetes mellitus, stroke, and dementia, 26–28 which are common in aging people. Wollina and Machetanz 29 reported that older age was a risk factor for herpes zoster and postherpetic neuralgia requiring hospitalization.…”
Section: Discussionmentioning
confidence: 99%